Analisis Fuzzy C-Means dan Penerapannya Dalam Pengelompokan Kabupaten/Kota di Provinsi Sulawesi Selatan Berdasarkan Faktor-faktor Penyebab Gizi Buruk - Wahidah Sanusi; Ahmad Zaki; Besse Nur Afni (Journal of Mathematics, Computations and Statistics, 2019)
In the analysis of clustering, many groups became an issue. Some researchers chose many groups that match the needs of their research. FCM performs grouping with the principle of minimising its categorization function where one of the parameters is a membership function in fuzzy (as weighing), also known as with fuzzier .This research aimed to study the methods of grouping with Fuzzy C-Means Clustering and its application in the classification of grouping at Regency/City of South Sulawesi based on factors of Causes of Malnutrition i.e. in terms of facilities and health workers, population, economy, and low nutrient intake that is low. From the results of the analysis of the classification with Fuzzy C-Means with 2 clusters with the objective function respectively is 1079141921.2224. When the first group of 18 district while the second group consists of 6 counties.